Orchestrating Sustainability: How Gender-Focused HRM and Tacit Knowledge Drive Sustainable Performance through Resource Orchestration Capability - Ikhah Malikhah; Batubara, Soulthan Saladin; Siregar, Oktarini Khamilah (International Review of Management and Marketing, 2026)
Organisations with comparable sustainability commitments often produce markedly different outcomes. Resource possession and equitable policy adoption explain part of this variation, but not enough. Drawing on resource orchestration theory and the resource-based view (RBV), this study argues that resource orchestration capability (ROC) is the mechanism through which gender-focused human resource management (GFHRM) and tacit knowledge translate into sustainable performance. Data came from a cross-sectional survey of 210 professionals across Indonesia’s food industry. All constructs were operationalised using a validated two-stage higher-order construct (HOC) approach in PLS-SEM; twelve first-order dimensions served as manifest indicators for four second-order constructs. Composite reliability (CR) exceeded 0.85 and average variance extracted (AVE) exceeded 0.65 for all constructs; HTMT ratios and the Fornell–Larcker criterion confirmed discriminant validity. GFHRM significantly predicted both ROC (β = 0.318, p < 0.001) and sustainable performance (β = 0.276, p = 0.002). Tacit knowledge had the strongest antecedent effect on ROC (β = 0.393, p < 0.001) and independently predicted sustainable performance (β = 0.297, p = 0.001). ROC in turn predicted sustainable performance (β = 0.324, p = 0.001) and partially mediated both upstream relationships: GFHRM (indirect β = 0.103, VAF = 27.17%) and tacit knowledge (indirect β = 0.127, VAF = 30.04%). PLSpredict confirmed out-of-sample predictive superiority over a linear benchmark across all twelve indicators. The findings establish ROC as a mediating mechanism, not a moderating condition, in the resource-to-performance pathway, and situate GFHRM within a capability-building framework rather than treating it as a standalone diversity intervention.